Pedagogical grammar - Keck, Casey; Kim, YouJin (Language teacher) (John Benjamins Publishing Company, 2014)
This book provides a comprehensive overview of pedagogical grammar research and explores its implications for the teaching of grammar in second language classrooms. Drawing on several research domains (e.g., corpus linguistics, task-based language teaching) and a number of theoretical orientations (e.g., cognitive, sociocultural), the book proposes a framework for pedagogical grammar which brings together three major areas of inquiry: (1) descriptions of grammar in use, (2) descriptions of grammar acquisition processes, and (3) investigations of the relative effectiveness of different approach.